The antibacterial activity of diluted Tualang honey - N. A. Roslan; H. N. Mohammad Rashed; N. H. Harun; Mohd Hafiz Jamaludin; Zulhisyam Abdul Kari @ Abdullah; A. R. Alimon (2015)
Tualang honey (TH) is a Malaysian jungle honey obtained from the wild. The honey is produced by the rock bee (Apis dorsata), which builds hives on branches of tall Tualang (Koompassia excelsa (Becc.) Taub) trees located mainly in the north-western region of Peninsular Malaysia. Limited information is available on the antibacterial mechanism of local honey. The present study was conducted to determine the antibacterial activity of diluted ‘Tualang’ honey against Escherichia coli (E. coli). Three different Tualang honey concentrations, namely, 20, 30 and 40% were used to examine the effect of diluting Tualang honey on its antibacterial effect towards E. coli. The 40% diluted honey was the most effective in inhibiting the growth of E. coli, followed by honey diluted at 20 and 30%. The high antibacterial activity of honey towards E. Coli was thought to arise from the production of hydrogen peroxide, but requires further study to validate the action